2016
DOI: 10.1155/2016/5691735
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for Service Routes of Pallet Service Center Based on the Pallet Pool Mode

Abstract: Service routes optimization (SRO) of pallet service center should meet customers' demand firstly and then, through the reasonable method of lines organization, realize the shortest path of vehicle driving. The routes optimization of pallet service center is similar to the distribution problems of vehicle routing problem (VRP) and Chinese postman problem (CPP), but it has its own characteristics. Based on the relevant research results, the conditions of determining the number of vehicles, the one way of the rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A variety of models such as deep neural networks, convolutional neural networks, and recurrent neural networks have been introduced and achieved good results [24][25][26]. e system based on the state output of the deep neural network has a certain decrease in error rate compared to the convolutional neural network, which proves the modeling ability of the neural network method in the field of English speech rationality optimization recognition [27,28]. However, the method for optimizing the rationality of English speech based on deep learning requires a large amount of training data to ensure its accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of models such as deep neural networks, convolutional neural networks, and recurrent neural networks have been introduced and achieved good results [24][25][26]. e system based on the state output of the deep neural network has a certain decrease in error rate compared to the convolutional neural network, which proves the modeling ability of the neural network method in the field of English speech rationality optimization recognition [27,28]. However, the method for optimizing the rationality of English speech based on deep learning requires a large amount of training data to ensure its accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the computational complexity, researchers have developed heuristics to solve the pallet pool operation model in the literature. Zhou et al 9 developed an immune clone algorithm (ICA) for a pallet allocation model, and it was proved more effective than the traditional genetic algorithm (GA). However, compared with some other evolutionary algorithms (EAs) as ICA and GA, PSO is easier to implement and fewer control parameters are needed.…”
Section: Particle Swarm Optimization Algorithm and Experimental Resultsmentioning
confidence: 99%
“…2,7 The closed-loop system is the most popular. 8,9 There is one issue which ever plagues the pallet industry-proprietary pallets that have leaked out of a closed-loop system. 10 Ilic et al 11 reported that the annual loss rate of pallets was about 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [20] dealt with uncertainty while optimizing the whole pallet allocation process, including buying (leasing), distribution, repositioning, and recovery. Assuming the pooler's perspective, Zhou et al [21] optimized the delivery and collection routes from the pooler's facility to the clients of the pallet management service. Tornese et al [22] quantified the effects of repair facility location and pallet service conditions (i.e., pallet handling and loading conditions) on a pooling system in accordance with economic and environmental performance.…”
Section: Literature Reviewmentioning
confidence: 99%